2018
DOI: 10.1177/0886260518777011
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Attitudes Toward Masculinity in Croatian Schools: Behavioral and Emotional Characteristics of Students Who Bully Others

Abstract: Prevention of bullying is paramount to creating a positive and welcoming school environment. This study compared the following characteristics reported by students who had perpetrated bullying in Croatian schools and those who did not: gender, type of school, family wealth, negative emotionality, behaviors that may compromise health, and endorsement of traditional masculinity. Within the framework of the "Croatian Adolescent Masculinity Study," second and third grade students of secondary schools (equivalent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Notably, growing evidence has shown that among adolescents those being bullied had the highest risk of suicidal behaviors [ 15 , 16 ]. Students who were bullied by their peers can lead to both physical and mental problems [ 17 ]. A cohort study has indicated that being bullied in adolescence is associated with elevated levels of suicidal behaviors that may persist into adulthood [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, growing evidence has shown that among adolescents those being bullied had the highest risk of suicidal behaviors [ 15 , 16 ]. Students who were bullied by their peers can lead to both physical and mental problems [ 17 ]. A cohort study has indicated that being bullied in adolescence is associated with elevated levels of suicidal behaviors that may persist into adulthood [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, those who engage in bullying perpetration at school are also at risk. For example, cross-sectional findings show that those who bully are more likely to report suicidal ideations (e.g., Gereš, Orpinas, Rodin, Štimac-Grbić, & Mujkić, 2021), and longitudinal findings show that children who engage in bullying perpetration are at higher risk of violent behavior in adulthood (Farrington, Lösel, Ttofi, & Theodorakis, 2012) and at higher risk of long-term psychosomatic problems, in comparison with uninvolved children (for a meta-analysis, see Gini & Pozzoli, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Concerns about men's physical and mental health are associated with complex factors that intersect with men's gender role socialization, and endorsement of traditional masculinity may harm health and wellbeing. The notion of masculinity in our society is frequently translated into the expectation "real men" should engage in activities that put them at risk for injuries and should be reluctant to seek help for health concerns (Robertson and Williams 2009;Gereš et al 2018).…”
Section: Introductionmentioning
confidence: 99%